Achieving best-fit configurations through advisory subsystems in AKIS: case studies of advisory service provisioning for diverse types of farmers in Norway. Issue 3 (27th May 2017) - Klerkx, Laurens; Petter Stræte, Egil; Kvam, Gunn-Turid; Ystad, Eystein; Butli Hårstad, Renate Marie
ABSTRACT: Purpose: In light of the discussion on 'best-fit' in pluralistic advisory systems, this article aims to present and discuss challenges for advisory services in serving various types of farmers when they seek and acquire farm business advice. Design/methodology/approach: The empirical basis is data derived from four workshops, five interviews with staff from advisory organizations, and interviews with 11 farmers. Findings: Emerging configurations serve different types of farmers, that is, private advisors serve different clients in different ways; these could be considered subsystems within the overall advisory system. Practical implications: Best-fit configurations of advisory services exist within a country setting in response to farmers' information demands and how they seek information, as well as public goals of the advisory system, and lead to advisory subsystems. Policy-makers should monitor the emergence of these subsystems and become active participants in some of them, in line with the concept of the public sector as regulator of private and commercial advisory systems. Theoretical implications: Best-fit has been mainly explored at country level, but this study shows that, within countries, different advisory service configurations are formed. So, best-fit should not be considered at national level only, in view of subsystems which can have wider or narrower boundaries. More broadly, the concept of Agricultural Knowledge and Innovation Systems (AKIS) should not be confined to the national level, for example, in view of farmer specializations within countries and the international dimensions of advisory systems. Originality/value: The originality lies in the further unraveling of heterogeneity within AKIS and what this implies for advisory service delivery configurations.